Propagation of three Blue Honeysuckle (Lonicera caerulea L.) cultivars in in vitro culture : Razmnožavanje tri kultivara sibirske borovnice u in vitro kulturi - Mihaljević, Ines (Array, 2019)
The aim of this study was to micropropagate three blue honeysuckle cultivars "Kalinka", "Polar Jewell" and "Balalaika". Driver and Kuniyuki medium (DKW) with different type and concentrations of plant hormones for in vitro shoot multiplication. For in vitro rooting was used Driver and Kuniyuki medium (DKW) and Murashige and Skoog medium (MS) with different concentrations of indol-3-butyric acid (IBA). The highest multiplication rate was obtained on DKW medium supplemented with 4 mg L-1 6-benzylaminopurine (BA) and 1 mg L-1 indole-3-butyric acid (IBA) for cultivars "Balalaika" and "Polar Jewell", while of cultivar "Kalinka" with DKW medium and 2 mg L-1 6-benzylaminopurine (BA) and 0.5 mg L-1 indole-3-butyric acid (IBA). The best microshoot rooting rates were obtained on DKW basal nutrient medium with 1 mg L-1 indol-3-butyric acid (IBA).